What Is The Comparative Effectiveness Of Radical Prostatectomy, Radiation Therapy, And Androgen Deprivation Therapy In Patients With Biochemically Recurrent Prostate Cancer After Initial Treatment? : A Systematic Review and Metaanalysist Studies - Tegar Pamungkas; John M.Sangkai (The Indonesian Journal of General Medicine, 2025)
Introduction: Biochemically recurrent prostate cancer (BCRPC) after initial treatment poses a significant clinical challenge. This systematic review and meta-analysis aimed to evaluate the comparative effectiveness of radical prostatectomy, radiation therapy, and androgen deprivation therapy (ADT), including novel antiandrogens, in patients with BCRPC without metastatic disease. Methods: Following PRISMA 2020 guidelines, 40 studies published within the last 10 years were included, comprising mostly randomized controlled trials and prospective cohorts. Eligible studies compared at least two interventions among radical prostatectomy, radiation therapy, and ADT in adult patients with biochemical recurrence after primary treatment. Primary outcomes included progression-free survival, metastasis-free survival (MFS), overall survival (OS), and treatment-related complications. Data extraction and quality assessment were performed independently by multiple reviewers. Results: The addition of ADT to salvage radiotherapy (SRT) significantly improved PSA progression-free survival (HR 0.63; 95% CI 0.53–0.74) and metastasis-free survival (HR 0.67; 95% CI 0.55–0.82). Longer ADT duration (24 months) was superior to shorter duration (6 months) in improving MFS (HR 0.77; 95% CI 0.61–0.97). Novel hormonal agents combined with ADT, such as apalutamide, abiraterone, and enzalutamide, further enhanced biochemical control (HRs ranging 0.48–0.72). No consistent overall survival benefit was observed across studies (HR 0.85; 95% CI 0.42–1.69). PSMA PET/CT-guided SRT improved biochemical progression-free survival compared to conventional imaging. Treatment-related toxicities increased with dose-intensified radiotherapy and intensified hormonal therapies but were generally manageable. Discussion: Combining ADT with SRT improves biochemical and metastasis-free outcomes in BCRPC patients. Extended ADT duration and novel antiandrogen additions show further benefit, though optimal timing and duration remain uncertain. Advanced imaging enhances treatment precision. Balancing efficacy with toxicity and quality of life is essential. Conclusion: Multimodal treatment involving salvage radiotherapy and ADT, especially with novel hormonal agents, improves disease control in biochemically recurrent prostate cancer. Personalized treatment decisions based on patient risk and PSA kinetics are crucial. Further research is needed to clarify overall survival benefits and optimize therapy duration.